1999
DOI: 10.1136/gut.44.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Dietary polyamines are essential luminal growth factors for small intestinal and colonic mucosal growth and development

Abstract: Background-Polyamines are essential for cell growth. Dietary and probably gut bacterial derived polyamines contribute significantly to the polyamine body pool. Aims-To evaluate the influence of dietary, luminal polyamines on growth and development of diVerent gastrointestinal organs in normally growing rats. Methods-Male suckling Wistar rats were randomly allocated to four treatment groups: polyamine deficient diet (PDD); PDD plus antibiotics (neomycin 2 g/kg and metronidazole 34 mg/kg); PDD plus polyamine sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(76 citation statements)
references
References 26 publications
1
70
0
4
Order By: Relevance
“…Arg is involved in the synthesis of polyamines, which in turn are associated with cell division, protein synthesis, and tissue growth (Pegg & McCann 1982) besides its nutritional importance for the growth and intestine development (Löser et al 1999). However, for Arg to be used in the synthesis of polyamines, it needs to be hydrolyzed into urea and ornithine by kidney arginase (Meijer et al 1990, Wu & Morris 1998, since ureotelic species do not synthesize ornithine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arg is involved in the synthesis of polyamines, which in turn are associated with cell division, protein synthesis, and tissue growth (Pegg & McCann 1982) besides its nutritional importance for the growth and intestine development (Löser et al 1999). However, for Arg to be used in the synthesis of polyamines, it needs to be hydrolyzed into urea and ornithine by kidney arginase (Meijer et al 1990, Wu & Morris 1998, since ureotelic species do not synthesize ornithine.…”
Section: Discussionmentioning
confidence: 99%
“…Putrescine is formed by the decarboxylation of ornithine, and spermine and spermidine are obtained from putrescine in the presence of decarboxylated S-adenosylmethionine, which is derived from methionine; thus both arginine and methionine are involved in their synthesis. These biogenic amines are also considered nutritionally important local factors for growth and the development of small intestinal and colonic mucosa (Löser et al 1999). Ruemmele et al (1999) had already reported that the lack of polyamines inhibits the proliferation, migration, and apoptosis of intestine cells.…”
Section: Introductionmentioning
confidence: 99%
“…The early studies have shown that intestinal and dietary polyamines can enhance colonic tumorigenesis, and can minimize the effects of ODC inhibitors (112). In tumor-bearing animal models, it has been demonstrated that a polyamine deficient diet significantly enhances the antitumoral effect of DFMO plus neomycin (113).…”
Section: Influence Of Dietary Polyamines On Crc Chemopreventionmentioning
confidence: 99%
“…Immune-stimulated animals may have an increased need for Arg due to its conversion into ornithine and production of polyamines, which play a key role in cell division, DNA synthesis and cell cycle regulation (Löser et al, 1999;Le Floc'h et al, 2004). Arginine acts as a potent modulator of phagocytosis mediated by macrophages through the synthesis of NO (Hibbs et al, 1987;Amber et al, 1991;Tsai et al, 2002), which stimulates local vasodilation and promotes tissue repair (Bredt and Snyder, 1994).…”
Section: The Effect Of Arginine Dietary Supplementation In Broiler Brmentioning
confidence: 99%